Kinetics Study in Essential Oil Extraction from Basil Leaves by Microwave Assisted Hydrodistillation - Putri, Ditta Kharisma Yolanda; Udroto, Firsta Retnaningtyas; Fatimah, Dianavita; Fachri, Boy Arief; Rahmawati, Istiqomah; Mumtazah, Zuhriah; Palupi, Bekti; Al Fajri, Maktum Muharja (Politeknik Negeri Malang, 2025)
Essential oil is compounds that contained in plants and have many benefits. Basil is an aromatic plant that can produce essential oils. Essential oils can be extracted from basil leaves using Microwave Assisted Hydrodistillation (MAHD) method. To determine the efficiency of the MAHD method, it’s necessary to study the kinetics of the extraction method. It’s because kinetic studies can be used to identify the optimal point in the process where the highest efficiency is obtained, so the extraction process can be optimized. The aim of this research is to evaluate the suitable kinetic model for the basil leaf extraction process using the MAHD method. This extraction using 100 grams of basil leaves and 200mL aquadest, heated at various microwave power 150W, 300W, and 450W. The extractions were carried out for 70 minutes with 10 min intervals. The results showed that the largest oil yield was obtained when using 450W power, which was 0.190 grams. Based on the experimental data obtained, the most suitable kinetic model is second-order model. This can be analyzed from the highest R2 (0.9946 – 0.9999) and the lowest RMSE (0.0062 – 0.0349). Increasing the irradiation power will affect the extraction rate and parameter values of each kinetic model.